Aplicación de estrategias metacognitivas para desarrollar la comprensión lectora de los alumnos de 5to de primaria de la I.E “Manuel Segundo del Águila Velásquez”, Ponazapa en el área de comunicación integral - Chetilán Gálvez, Neiser (2012)
At present we are living in a distinguished society for the great quality of the information that it is published for different writings media, it is so the information either of scientific eventses and not scientific reach to the peoples by means of the writing language, therefore springs up the need to educate to the human beings in the ability of reading comprehension; then the education plays a very important paper in which is must educate to the child to learn to learn, in this way springs up the application of the "Metacognitivas strategies" in the reading comprehension in the process of teaching-apprenticeship; that it permits to the student it learns to learn, to improve the reading comprehension in your three levels. By having knowledge of the multicavity perspectivas and exigencias that the Peruvian education proposes, requires and needs educational pharmaceutical preparations, qualified, skilled delivered nevertheless the care and vocation to the pedagogic field where your unique interest is to propose, to fortify and search for new improvements and methodologies of teaching. The metacognición consists in which the individual knows your own process of apprenticeship, the conscious programming of strategies of apprenticeship, of memory, of solution of problems and takes of decisions and, then, of selfregulation; and so it can transfer thoses contained to other situations or similar actions. Of this perspectiva the objective of investigation this letter was to demonstrate the significant influence of the "Metacognitivas strategies" in the reading comprehension of the students of fifth degrees of primary education of the educational institution Emmanuel Segundo Velasquez of the eagle- Ponazapa in the area of communication. lnvestigation lays the foundations of in the theories: Ausubeliana of Ausubel, genetics of Piaget and partner, cultural of Vygotsky, of similar way, the investigation is of applied type of the experimental leve!, with design almost, experimental of jpretestl- ¡postestl with two groups: control group with thirty and two (32) students of the fifth harrow "B" and the experimental group with thirty and one (31) students of the fifth harrow "A", obtaining Te =, 8.04 and t =, 1.699 beinga = 0.05.